1978
DOI: 10.1104/pp.62.5.833
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Low Temperature, Water Stress, and Short Days in the Induction of Stem Frost Hardiness in Red Osier Dogwood

Abstract: The induction of stem frost hardiness by low temperature, water stress, short days, and their combinations in 2-and 4-month-old growing dogwoods ( Cornus stolonifera) were investigated. When plants were subjected to more than one factor, the increased hardiness was the sum of the effects of the individual factors involved. No interactions among these factors on hardiness were observed during a 3-week treatment. Results indicate that low temperature, water stress, and short days initially trigger independent fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…However, 1-week-old seedlings (no epicotyl, cotyledons only) were unable to increase their frost tolerance. Chen and Li (1978) also reported similar results for Cornus stolonifera Michx. seedlings, with the greatest frost tolerance occurring under a combination of low temperature and short photoperiod.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, 1-week-old seedlings (no epicotyl, cotyledons only) were unable to increase their frost tolerance. Chen and Li (1978) also reported similar results for Cornus stolonifera Michx. seedlings, with the greatest frost tolerance occurring under a combination of low temperature and short photoperiod.…”
Section: Introductionsupporting
confidence: 82%
“…Brown and Bixby (1976) reported the same type of reaction for Robinia pseudoacacia L., in which 4-week-old seedlings were unable to react to a hardening treatment while 8-, 12-, and 16-week-old seedlings did, and their degree of frost tolerance increased with chronological age. Chen and Li (1978) also found that 12-week-old Cornus stolonifera seedlings had a greater response to a low-temperature treatment compared with 8-week-old seedlings. Neither of these studies, however, indicates the developmental stage of seedlings at the beginning of the treatment or when they were freeze tested.…”
Section: Hardening Capacity Of Different Developmental Stagesmentioning
confidence: 85%
“…2, Table 3). Low temperature induced dehydration in plant tissues has been proved by molecular and physiological evidence (Chen and Li 1978;Mantyla et al 1995;Rajashekar and Panda 2014). In the present study, a short-term low temperature significantly reduced Ψ l , RWC, Ψ o and g s in leaves of both the drought-primed and non-primed plants (P<0.001).…”
Section: Discussionmentioning
confidence: 54%
“…However, further decrease in water potential after 6 days of water withholding did not affect the freezing tolerance suggesting that the initial water stress was able to induce freezing tolerance. Thus, it is likely that water stress can trigger the cold acclimation process and can independently induce freezing tolerance in plants (Chen and Li, 1978). Mantyla et al (1995) compared freezing tolerance in Arabidopsis induced by water stress and cold acclimation treatment and found that water stress alone could induce freezing tolerance to similar levels as the cold acclimation treatment.…”
Section: Water Stress and Induction Of Freezing Tolerancementioning
confidence: 99%